Cameroon Juvenocracy: Youth-shaped IGA : A Tale of Two Countries: Labor Market Profiles of Youth in Urban and Rural Cameroon - Botea, Ioana Alexandra; Del Bono, Mitja (Washington, DC: World Bank, 2022)
Low productivity - rather than absolute employment levels - is the main labor market challenge in Cameroon, where vulnerable employment in the form of subsistence farming or self-employment in the informal sector remains the norm. Low-skill, low-pay agricultural work is prevalent in rural areas, while more productive employment in urban areas is increasingly accompanied by high unemployment and inactivity among educated youth holding out for public sector jobs. Labor market vulnerability, either detachment or weak-attachment, is thus particularly acute among youth (ages 15 to 35), who are often uninterested in agriculture and unable to access better opportunities in urban areas. Using an advanced statistical technique, the authors identify distinct profiles of youth experiencing labor market vulnerability. The largest group in urban areas (35 percent) consists of men with some education who work full-time in the informal sector. In rural areas, almost half (45 percent) of youth continue to work the land at a subsistence level. A clear pattern of gender inequality emerges: all detachment groups are majority women, with high inactivity rates among married women in rural areas and highly-educated but discouraged women in urban areas. Women are also overrepresented among the most vulnerable employed groups, especially in rural areas where they often work as unpaid family support.Tailored employment support interventions are, therefore, needed to promote inclusive productivity and effectively utilize the country’s human capital.